2020
DOI: 10.2147/jpr.s225230
|View full text |Cite
|
Sign up to set email alerts
|

<p>No Differences in the Prevalence and Intensity of Chronic Postsurgical Pain Between Laparoscopic Hysterectomy and Abdominal Hysterectomy: A Prospective Study</p>

Abstract: Objective: To compare the prevalence and characteristics of chronic postsurgical pain (CPSP) between laparoscopic hysterectomy (LH) and abdominal hysterectomy (AH) groups 3, 6, and 12 months after surgery, and to assess the impact of pain on the activities of daily living (ADL) of patients. Methods: The demographic characteristics, intraoperative clinical factors, and postoperative pain score were collected prospectively in patients scheduled for elective LH or AH for benign disease at our institution from Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…However, a minimally invasive technique may not reduce CPSP incidence after colorectal surgery, as observed in our study. Similarly, previous studies have also reported no decrease in the prevalence of CPSP after other surgeries, such as hysterectomy [9], nephrectomy [42] or thoracotomy [43], with the use of laparoscopic or video‐assisted surgical approaches.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, a minimally invasive technique may not reduce CPSP incidence after colorectal surgery, as observed in our study. Similarly, previous studies have also reported no decrease in the prevalence of CPSP after other surgeries, such as hysterectomy [9], nephrectomy [42] or thoracotomy [43], with the use of laparoscopic or video‐assisted surgical approaches.…”
Section: Discussionmentioning
confidence: 55%
“…Chronic postsurgical pain (CPSP) is defined by the International Association for the Study of Pain (IASP) as the pain that develops after surgery and persists for at least 3 months [1]. CPSP is increasingly being recognized as a frequent complication after diverse surgical procedures, including thoracotomy (incidence of CPSP 25%-60%) [2,3], mastectomy (20%-50%) [4,5], herniotomy (5%-12%) [6,7], hysterectomy (5%-32%) [8,9], caesarean section (6%-18%) [10,11] and amputation (50%-80%) [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative pain was evaluated using a NRS ranging from 0 (no pain) to 10 (maximum imaginable pain). 6 The highest NRS scores of the patients were recorded in 0-2 hours, 2-8 hours and 8-24 hours after reaching PACU (0 hours). In the case of postoperative pain with an NRS score of ≥5, 50 mg IV dexketoprofen (Deksalgin; Nobel Ilac, Istanbul, Turkey) was administered.…”
Section: Postoperative Periodmentioning
confidence: 87%
“…3 Severe pain may occur in the postoperative period of septorhinoplasty due to soft tissue injury and osteotomies. 5 On a numerical rating scale (NRS) 6 from 0 to 10, a pain score of >3 in 45% of patients and a pain score of >6 in almost 30% of patients were reported after a septorhinoplasty operation. 7 In their study examining the postoperative pain of patients undergoing rhinoplasty operation, Demir et al accepted patients with an NRS score of ≥5 as patients with postoperative pain and applied analgesics to them.…”
Section: Introductionmentioning
confidence: 99%